2022
DOI: 10.1503/cmaj.220919
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant use and associated outcomes in older patients receiving home palliative care: a retrospective cohort study

Abstract: Background:The benefits and harms of anticoagulants for people near the end of life are not well understood, nor is it known what proportion of patients discontinue these medications. We aimed to characterize anticoagulant use in older recipients of home palliative care and describe patient and provider characteristics, as well as outcomes associated with anticoagulant discontinuation in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Anticoagulant use among older American nursing home residents with atrial fibrillation who are entering hospice has not been well described. One study of older adults in Canada receiving home palliative care found that one in four OAC users discontinued anticoagulants after their first home palliative care visit 22 . In this prior study, the percentage who discontinued OACs prior to the start of palliative care was not reported.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Anticoagulant use among older American nursing home residents with atrial fibrillation who are entering hospice has not been well described. One study of older adults in Canada receiving home palliative care found that one in four OAC users discontinued anticoagulants after their first home palliative care visit 22 . In this prior study, the percentage who discontinued OACs prior to the start of palliative care was not reported.…”
Section: Discussionmentioning
confidence: 83%
“…We also tracked the presence of any hospitalizations with inpatient surgery in the past 6 months, as acute events arising in hospitalizations that may affect clinical decision making. From the MDS, we included a history of recent falls (J1800), rejected evaluation or care (E0800), cancer diagnosis (I0100), cognitive impairment based on the Cognitive Function Scale 25 and self-performance of activities of daily living (ADLs) as (low functional dependency [0-7], mild functional dependency [8][9][10][11][12][13][14], moderate functional dependency [15][16][17][18][19][20][21], and high functional dependency [22][23][24][25][26][27][28]). 26 We created a categorical variable that indicated the index date year.…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dabei orientierten sich diese stark an der basalen Funktionalität. Eine große Studie aus der palliativen häuslichen Pflege in Kanada zeigt, dass Antikoagulantien häufig (Prävalenz 15 %) auch in diesen Situationen noch verordnet werden, aber im Verlauf in etwa 25 % der palliativen Patienten abgesetzt werden, wobei kein direkter Einfluss der Diagnose oder von klinischen Aspekten des Patienten festgemacht werden konnte [17]. Diejenige Gruppe, bei der die Antikoagulantien abgesetzt wurden, zeigte eine etwas erhöhte Mortalität, eine geringere Blutungsinzidenz, aber kein eindeutiges, vermehrtes Auftreten von thromboembolischen Ereignissen.…”
Section: Frailty Und Allgemein Eingeschränkte Funktionalitätunclassified